The importance of assessing priorities of reproductive health concerns among adolescent and young adult patients with cancer. Issue 15 (5th June 2015) - Murphy, Devin; Klosky, James L.; Reed, Damon R.; Termuhlen, Amanda M.; Shannon, Susan V.; Quinn, Gwendolyn P.
<x xml:space="preserve">Abstract</x> Visions for the future are a normal developmental process for adolescents and young adults (AYAs) with and without cancer, and these visions often include expectations of sexual and romantic relationships. AYA cancer survivors indicate reproductive health is an issue of great importance and more attention is needed in the health care setting throughout the cancer experience, beginning at diagnosis. Various practice guidelines are predominately focused on fertility; are intended to influence survivorship care plans; and do not encompass the broad scope of reproductive health that includes romantic partnering, friendships, body image, sexuality, sexual identity, fertility, contraception, and more. Although interventions to reduce reproductive health‐related sequelae from treatment are best approached as an evolving process, practitioners are not certain of the priorities of these various reproductive health content areas. Strategies incongruent with the reproductive health priorities of AYAs will likely thwart adequate follow‐up care and foster feelings of isolation from the treatment team. Research is needed to identify these priorities and ensure discussions of diverse content areas. This review explored various domains of reproductive health and emphasized how understanding the priorities of the AYA cancer cohort will guide future models of care. Cancer 2015;121:2529–2536. © 2015 American Cancer Society.